The impact of the COVID-19 pandemic on the females' Intention to buy clothes Online in Makkah region - Elias, Tahany Abdullah AbdulBaqi; Abalkhail, Tagreed Saleh Ali (Journal of Humanities & Social Sciences, 2023)
The (COVID-19) pandemic during the year of 2020 and its impact on the conditions of precautionary closure and home quarantine in the Makkah region, contributed to the trend towards online purchases. Applying descriptive method, the aim of the study is to know the impact of the Covid-19 pandemic crisis on the intention to buy clothes online using the theory of planned behavior, by studying the correlation between the repercussions of the crisis related to consumption and the intention to buy clothes online. The results showed high consumers' behavioral control of buying clothes preparing for seasons while the desire to spend money for buying clothes is decreased. The result also confirmed the relation between the buying intention and health, social and psychological preventive measures during the pandemic, so that the impact of crises on the behavior of clothing purchase is evident, so, it is necessary to ascertain the consequences of the pandemic's impact on the behavior of the practice of online consumption, especially related to the psychological feelings of the consumer, and how they relate to the quality of human life at various levels.
Keywords: Clothes; Purchases Intention; Correlation; (COVID-19) pandemic